The Impact of Risk Management and Capital Adequacy Ratio on Banking Performance in Indonesia - Kurrota A'yuni Aisy; Elfrida Eufunny; Henny Setyo Lestari; Farah Margaretha Leon (Majapahit Journal of Islamic Finance and Management, 2026)
This research examines the impact of risk management practices and capital adequacy on banking performance in Indonesia. Bank performance is measured by Return on Assets, while risk management is represented by credit, market, liquidity, and operational risk indicators. Capital Adequacy Ratio is used as a proxy for capital strength, with firm size and firm growth rate serving as control variables. The study applies a quantitative approach using secondary data from the financial statements of 43 commercial banks listed on the Indonesia Stock Exchange during the 2020–2024 period and employs panel data regression with a fixed effects model. The results indicate that the variables jointly have a significant effect on banking performance. Partially, Loan Loss Provision, Operating Expense Ratio, Efficiency Ratio, and Capital Adequacy Ratio have a positive and significant impact on Return on Assets, while the remaining risk indicators and control variables do not show significant effects. These findings indicate that effective credit provisioning, operational efficiency, productive cost management, and adequate capital strength are key factors in improving banking performance and maintaining sector stability.